Explaining the relationship between religiosity and increased wellbeing avoidance of identity threat as a key factor. Issue 2 (3rd April 2021) - Phillips, Rita; Connelly, Vincent; Burgess, Mark
ABSTRACT: Previous research outlines a relationship between religiosity and increased mental and physical wellbeing. However, to date findings from quantitative and qualitative research do not offer an unambiguous explanation for this relationship. The study addresses this gap in knowledge by examining underlying identity construction processes in relation to religiosity and wellbeing in the light of Identity Process Theory. Eight Christian converts from different deep-faith groups were recruited via purposive and modified snowball sampling. Detailed descriptions of first-hand experiences were collected by biographic-narrative interviews and analysed by Interpretative Phenomenological Analysis. The findings suggest that religious elements are integrated into identity content as these respond to a set of motivational principles of identity construction. In doing so, religious elements in identity content contribute to the avoidance of identity threat and to the maintenance of a positive identity structure. The adoption of health-promoting behaviours that relate to the application of beliefs (i.e. practice forgiveness, love oneself and the other, stopping excessive drinking) are consequences thereof and improve mental and physical wellbeing. In conclusion, the relationship between religiosity and wellbeing may be explained by the way in that religious elements in identity impact on identity maintenance process.